Effect of Fish Consumption Patterns on Stunting Toddlers in the Lowlands of South Kalimantan Province, Indonesia - Ahmad Suhaimi (Budapest International Research and Critics University, 2022)
This study aims to determine effect of fish consumption patterns on stunting toddlers in the lowlands of South Kalimantan Province, Indonesia. This type of research is descriptive quantitative research. Data collection methods in this study used several methods including observation, interviews, 24-hour recall, and documentation. The analytical technique used is multiple linear regression analysis using the SPSS 20 application. The results show that amount of fish consumption and frequency of fish consumption have a simultaneous effect on incidence of stunting. Coefficient of determination, amount of fish consumption and frequency of fish consumption effect on incidence of stunting by 43.8%. The partial significant test results show that amount of fish consumption has a significant effect on incidence of stunting, and frequency of fish consumption has a significant effect on incidence of stunting.